Effectiveness of Red Ginger (Zingiber Officinale Var. Rubrum) Hydrogel Extract as a Fever Reducer in Mice (Mus Musculus) - Syafril S. Panna; Irna Diyana Kartika; Andi Alamanda Irwan; Abdul Mubdi Ardiansar; Suci Noviyanah Anshary (Majalah Kedokteran Bandung, 2025)
Fever is a common physiological response to infection, and its management is crucial to prevent complications such as dehydration and organ damage. While pharmacological treatments like antipyretics are commonly used, there is a growing interest in exploring natural alternatives. Red ginger (Zingiber officinale var. rubrum) has shown potentials as a natural antipyretic due to its active compound, gingerol, which inhibits prostaglandin synthesis and reduces inflammation. This study aimed to evaluate the efficacy of red ginger-based hydrogel formulations in managing fever. Male albino mice were used as test subjects, with fever induced via subcutaneous injection of peptone solution. Three concentrations of red ginger extract (3%, 5%, and 10%) in hydrogel form were tested. Temperature changes were recorded at 15-minute intervals for 60 minutes post-treatment. Results showed that the 5% red ginger hydrogel formulation demonstrated the most significant temperature reduction, with an average decrease of 8.2°C when compared to 4.65°C in the 3% formulation and 4.45°C in the 10% formulation. The 5% formulation also displayed optimal physical properties, including viscosity and pH stability, ensuring efficient absorption of the active compounds. The 10% formulation showed reduced effectiveness due to its high viscosity, which impaired absorption. In conclusion, the 5% red ginger hydrogel formulation is the most effective concentration to reduce fever, highlighting its potential as a natural, affordable, and accessible alternative to conventional antipyretic treatments. Future studies should further explore its clinical applications and scalability in diverse healthcare settings